Centralized database for test operation - Gelera, Catherine G. (Animo Repository, 2021)
This action research intends to align and organize the machine records of Test Operations by creating a centralized database. Guided by the Five Lean Principles, the action research will address the delay in data and report generation as well as helping the user to become self-sufficient. The first cycle is focused on defining the problem, data collection, and database generation. The problem is broken down into manageable pieces by applying the root cause analysis (RCA) tools like the fishbone diagram and five why analysis. Then the value stream map (VSM), fishbone diagram, and five why the analysis was integrated to formulate the right issue or problem to solve and the action items on how it will be addressed. The PDCA cycle provides a systemic approach to how the team will execute the project according to plan. There are three defined areas for data collection, Pre-Test, Test, and Backend-Finishing. The first cycle will only cover the Test area and the remaining two areas will be covered in the second cycle. The second cycle covers the inclusion of the Backend-Finishing and Pre-test dataset to the centralized database. It will also capture the feedbacks and suggestions from the users after launching the initial centralized database which is for the Test area only. Standard procedure was also stated to define who is responsible for updating the database and the frequency of the update.